Hubungan religiusitas terhadap kualitas hidup (quality of life) pada pelajar di SMA Lampung - Alisah Rahmah Hidayah; Teguh Pribadi; Prima Dian Furqoni (Program Studi Ilmu Keperawata Fakultas Ilmu Kesehatan Universitas Malahayati, 2023)
Background: The many phenomena that occur in adolescence both in the world and in Indonesia, especially in Lampung, in previous research, stated that this case was due to the lack of good religious education. Because religiosity can influence individual feelings to form an optimistic quality of life for adolescents.Purpose: To find out whether there is a significant relationship between religiosity and quality of life for students at Bahrul Ulum Natar High School, South Lampung and public high school 1 Lemong Pesisir Barat, totaling 538 students.Method: Researchers used a descriptive correlation study with a proportional stratific random sampling technique, a research instrument CFA (Confirmatory factor analysis) and WHOQOL-BREF quality of life.Results: The level of religiosity obtained an average value of (2.7742) at Bahrul Ulum High School and (3.1545) at Public high school 1 Lemong. The level of religiosity in the two institutions related to the acquisition of high religiosity results was 9 (5.8%) at Bahrul Ulum High School and 46 (29.9%) at public high school 1 Lemong. The level of good quality of life in both institutions is related to the number of 10 (6.5%) at Bahrul Ulum High School, 50 (32.5%) at Public High School 1 Lemong. Based on the research results, it is known that there is a relationship between religiosity and quality of life for students at High School Lampung (p-value <0.05).Conclusion: The value of religiosity in both institutions has a high value with a good quality of life and there is a relationship between Religiosity and the Quality of Life of Students in High school Lampung with a p-value (<0.05).Keywords: Adolescents (Students); Quality of Life; ReligiosityPendahuluan: Banyaknya fenomena- fenomena yang terjadi pada usia remaja baik didunia maupun di Indonesia khususnya di Lampung, pada penelitian yang di lakukan sebelumnya, menyatakan adanya kasus tersebut dikarenakan belum tercapainya pendidikan religius yang baik. Karena religiusitas dapat mempengaruhi perasaan individu untuk membentuk kualitas hidup yang optimis bagi remaja. Tujuan: Untuk mengetahui apakah ada hubungan yang signifikan antara religiusitas dan kualitas hidup (Quality of life) pada pelajar di SMA Bahrul Ulum Natar Lampung Selatan dan SMAN 1 Lemong Pesisir Barat yang berjumlah 538 siswa.Metode: Penelitian deskriptif korelasi dengan teknik pengambilan sampel proportionate stratific random sampling, instrument penelitian CFA (Confirmatory factor analysis) dan quality of life WHOQOL-BREF.Hasil: Tingkat religiusitas didapatkan nilai rata-rata (2.7742) pada SMA Bahrul Ulum dan (3.1545) di SMAN 1 Lemong. Tingkat religiusitas dikedua institusi terkait didapatkan hasil religiusitas tinggi sebanyak 9 (5.8%) di SMA Bahrul Ulum dan 46 (29.9%) pada SMAN1 Lemong. Tingkat kualitas hidup baik pada kedua institusi terkait dengan jumlah 10 (6.5%) di SMA bahrul ulum, 50 (32.5%) pada SMAN 1 Lemong. Berdasarkan hasil penelitian diketahui bahwa ada hubungan antara religiusita dan kualitas hidup (Quality Of Life) pada pelajar di SMA Lampung (p-value < 0,05).Simpulan: Nilai religiusitas di kedua institusi bernilai tinggi dengan kualitas hidup baik serta terdapat hubungan antara religiusitas Terhadap Kualitas Hidup Terhadap Pelajar di SMA Lampung dengan P-value (<0.05).